Social media consumption in Klang Valley: Generation Z's desired content of Instagram - Kee, Chian Yue (2024)
Knowing the preferences and the habits of the Gen Z, the influential social media marketing targets, is very important for marketers and the brands that operate in the fast-paced world of social media marketing. This study discusses how Gen Z uses the highly popular Instagram as a content discovery and ad interaction platform and what various brands can do to provide Gen Z with content they truly enjoy. An online survey with 150 Gen Z participants at Klang Valley, Malaysia was utilized, and results obtained from quantitative method. According to the findings, Instagram is very much a Gen Z app, they actively consume contents like talent showing, meme sharing and more. Under the Uses and Gratifications Theory studying the patterns of behavior of Generation Z, the investigation emphasizes the priority activities of this generation, including liking, sharing stories, and sending direct messages that trend due to amusement. These findings provided detailed information on how to come up with an effective digital strategy that creates a sustainable relationship with the Gen Z group.